A BOOK REVIEW ARTICLE: LOOKING INTO ENGLISH LANGUAGE TEACHING IN EAST ASIA THROUGH TWIN VOLUMES - Bambang Yudi Cahyono (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
LANGUAGE POLICIES and LANGUAGE EDUCATION The Impact in East Asian Countries in the Next Decade. (2nd eeL). Edited by Ho Wah Kam and Ruth Y. L. Wong Language Singapore: Eastern Universities Press. 2004, xiv + 384 pp. ISBN: 9812103376